Congenital bronchopulmonary cystic disease. - Mendes, J (1998)
From September 1989 to December 1994, 12 children with congenital bronchopulmonary cystic disease were operated in the Department of Pediatric Surgery, Santa Maria Hospital. Four cases of bronchogenic cyst (BC), 2 of cystic adenomatoid malformation (CAM), 3 of pulmonary sequestration (PS), and 3 of congenital lobar emphysema (CLE) were found. Age ranged between 9 days and 10 years without predominance of gender. Seven were younger than one year of age, of which 5 were less than 6 months old at the time of surgery. The CAT scan was most useful in the diagnosis and follow-up of these children. The review of these cases helped evaluate our experience in the diagnosis and surgical approach for these congenital malformations. Successful treatment depends on early diagnosis and the planning of therapeutic priorities, based on the embryological and pathophysiological knowledge at these anomalies. The embryological mechanisms implicated in the development are discussed and the results of surgical treatment are presented.